Pengaruh Struktur Modal dan Carbon Emission Disclosure terhadap Nilai Perusahaan - Sungging Pinilih Chandra Asmara; Naila Najihah (Komunitas Dosen Indonesia, 2025)
In the era of sustainability and transparency, carbon emission disclosure and capital structure management have become critical considerations in assessing corporate value, particularly within high-emission industries such as the energy sector. This study aims to analyze the effect of capital structure and carbon emission disclosure on firm value in Indonesian energy companies. This study employs a quantitative method with an ex post facto research design, relying on secondary data obtained from financial statements and sustainability reports. A total of 44 energy companies listed on the Indonesia Stock Exchange during the period 2021–2023 serve as the units of analysis. The findings show that capital structure, as measured by the debt-to-equity ratio, has a significant negative effect on firm value, while carbon emission disclosure does not exhibit a significant influence. These results imply that a higher proportion of debt may reduce investor confidence and perceived firm value, whereas carbon emission disclosure alone, without concrete environmental initiatives, is insufficient to enhance firm value. Therefore, to improve firm value and strengthen their sustainability image, energy companies should maintain an optimal capital structure while ensuring that carbon emission disclosures are integrated into a broader, actionable sustainability strategy.